The possibility of utilization of tamper-evident bands (TEB) as fibers in concrete blends - Abdullah, Sarmad Fadhil; Abdulwahid, Mohanad Yaseen; AL-qasem, Imad Adel (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The impact of tamper-evident bands (TEB) as fiber on the distinctive properties of concrete was examined through a few laboratory tests. In this study, the tamper-evident band (TEB) is the plastic ring left around the neck of bottled drinking water. The properties examined incorporate workability, compressive strength, flexural strength, and splitting tensile strength at 7 and 28 days of moist curing. Three varied fiber volumes were added to concrete mixes at 0.5%, 1.0%, and 1.5% by volume of concrete. The test results show that the employment of 1% (TEB) fibers by volume of concrete lead to the increment of flexural and splitting tensile strengths of concrete 34.5% and 38.56% respectively in comparison to the reference concrete at 28 days of moist curing. It can be inferred, according to a preliminary analysis, that tamper-evident bands (TEB) are modern forms of fibers that have a good effect on the improvement of concrete's tensile properties.